Single machine batching problem to minimize the sum of completion times with number of batches and batch size limitations - Kanesan , Muthusamy; Ishii, Hiroaki; Mohri, Shintaro; Teruo, Masuda (International Society of Mathematical Sciences, 2001)
We consider single machine batch scheduling problem for identical jobs. Constant processing times and batch setup times are assumed together with batch size and number of batch constraints. We present a polynomially bounded algorithm that minimizes the sum of completion times. (Abstract by authors)